The effect of land inheritance on youth employment and migration decisions: Evidence from rural Ethiopia - Kosec, Katrina; Ghebru, Hosaena; Holtemeyer, Brian; Mueller, Valerie; Schmidt, Emily (International Food Policy Research Institute, 2016)
How does the amount of land youth expect to inherit affect their migration and employment decisions? This paper explores this question in the context of rural Ethiopia using panel data from 2010 and 2014. We estimate a household fixed-effects model and exploit exogenous variation in the timing of land redistributions to overcome endogenous household decisions about how much land to bequeath to descendants. We find that larger expected land inheritances significantly lower the likelihood of long-distance permanent migration and of permanent migration to urban areas during this time. Inheriting more land is also associated with a significantly higher likelihood of employment in agriculture and a lower likelihood of employment in the nonagricultural sector. Conversely, the decision to attend school is unaffected. These results appear to be most heavily driven by males and by the older half of our youth sample. We also find several mediating factors matter. Land inheritance plays a much more pronounced role in predicting rural-to-urban permanent migration and nonagricultural-sector employment in areas with less vibrant land markets and in relatively remote areas (those far from major urban centers). Overall, the results suggest that inheritance strongly influences the spatial location and strategic employment decisions of youth.